Effect of vitamin D on depression: an experimental study - Kolla, Rohan; Majagi, Suneel I. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: There is a scarcity of studies regarding antidepressant activity of vitamin D in animals while there are some contradictory reports regarding the same in humans. Therefore the present study was planned to investigate the antidepressant effect of vitamin D and its interaction with standard antidepressant drugs in animals. Methods: Forced swim test (FST) in adult male Wistar rats and tail suspension test (TST) in adult male Swiss albino mice were used to investigate antidepressant activity of vitamin D administered in single dose and multiple doses. Imipramine, a tri-cyclic antidepressant and fluoxetine, a selective serotonin reuptake inhibitor were used as standard antidepressant drugs. For interaction studies, half the therapeutic equivalent dose of vitamin D was combined with sub-effective dose (SED) of imipramine or fluoxetine. Data was expressed as Mean±SD and analyzed by standard statistical tests. P<0.05= significant. Present study was ethically approved. Results: Single dose administration of vitamin D did not show significant antidepressant effect either in FST or TST. Multiple dose administration of vitamin D showed significant antidepressant activity in TST but not in FST. Combination of vitamin D (half dose) with SED of either standard antidepressant drugs did not show any significant antidepressant activity. None of the treatment groups showed any significant difference on locomotor activity. Conclusions: In the present study, multiple dose administration of vitamin D showed some antidepressant activity. Further studies are needed to confirm and elaborate the role of vitamin D in behavioral disorders like depression.